Human Capital Downturn Effect on Firm Performance in Tourism and Hospitality Industry - Arya Aji Aditya; Cindy Olivia Angkasaputra; Hesti Wahyuni (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2022)
The objective of this study was to investigate the relationship between human capital and firm performance in the hotel, restaurant, and tourism industry periode 2019-2020. This is quantitative study that provides use of the mutilple linear regression method. The secondary data collection was obtained at www.idx.co.id, including income statement and financial statement notes for period 2019-2020. The analaysis result show that human capital has an effect on a firm performance. Based on the analysis result, we can conclude the COVID-19 pandemic has forced firms to implement human capital strategic planning such as layoffs, voluntary salary reductions, and reduced working hours, all of which have a detrimental effect on firm performance.